2005
DOI: 10.1097/01.dad.0000142240.93956.cb
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Trichoblastic Carcinoma Arising in Trichoblastoma

Abstract: It has been debated whether malignant transformation of trichoblastoma occurs. The concept was recently forwarded that basal cell carcinoma is as a malignant neoplasm of follicular germinative cells and should be named trichoblastic carcinoma to show its relationship to trichoblastoma. Almost all basal cell carcinomas are low-grade malignant neoplasms and develop metastases only very rarely, and if so, only after very long duration and untreated growth. Only rare basal cell carcinomas arise in trichoblastomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(14 citation statements)
references
References 9 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…The alternative available treatment was thallium acetate, which could induce nephritis and paralysis. Population studies have shown that patients who received depilatory radiotherapy for ringworm during childhood have a significantly higher risk of developing tumors, particularly in the cephalic area [4,5,6, 12]. Different types of cutaneous and noncutaneous cancers, especially brain, parotid and thyroid tumors [13, 14], have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative available treatment was thallium acetate, which could induce nephritis and paralysis. Population studies have shown that patients who received depilatory radiotherapy for ringworm during childhood have a significantly higher risk of developing tumors, particularly in the cephalic area [4,5,6, 12]. Different types of cutaneous and noncutaneous cancers, especially brain, parotid and thyroid tumors [13, 14], have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it has not been described after X-ray radiation. It is characterized by a propensity for local recurrence and potential metastatic spread [10,11,12]. This behavior differs substantially from TB or BCC.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] BCC is the most common malignancy worldwide in white people 19 and accounts for 65-75% of all skin tumors. 20 It originates from pluripotential primordial germ cells and founds in basal layer of epidermis and cutaneous appandages resembling the structure of hair follicle morphologically.…”
Section: Introductionmentioning
confidence: 99%
“…malignant mixed tumour, microcycstic adnexal carcinoma), that have been well established as entities up to now [3]. A partly malignant transformation of DT seems to be rare, but possible, in cases of multiple familial trichoepithelioma (Brooke–Spiegler syndrome) [46]. Malignant transformation of the complete DT has not yet been described.…”
Section: Introductionmentioning
confidence: 99%